Special exercises for numerical shortage in playing centers to develop some physical abilities of youth basketball players - Ahmed Mohammed Al-Shammari, Elaf (International Journal of Psychosocial Rehabilitation, 2020)
The importance of researching exercises for numerical deficiency according to the centers of playing in basketball and its effect on developing some physical abilities of young basketball players: the game of basketball is like any important team game that has its basic principles that it has become necessary to strive to find the best methods. Training to overcome the situations that occur during the match, especially the numerical shortage (leaving a player due to injury, committing a mistake, fatigue, nervous tension and even an offensive or defensive tactical change or both) that occurs during play due to the exclusion or change of players and the absence of substitute players (the same The playing center has the same level and performance, physical fitness, experience, training age, height, speed, and skill in defense, attack, and individual and collective tactics. Therefore, the researcher used exercises related to numerical deficiency and its effect on the development of some physical abilities of youth basketball players. The researcher used the experimental method for its suitability and the nature of the research. The research sample consisted of the Armenian Youth Sports Club, whose number is 12 players. The researcher concluded that the exercises for the normal deficiency had an effective effect in developing the speed of response and the strength characteristic of the speed by adapting the exercises to the age and training phase of the research sample.